Video Animasi Berbasis Augmented Reality untuk Meningkatkan Pemahaman Konsep IPAS Peserta Didik Kelas V SD: Augmented Reality-Based Animated Videos to Improve Fifth Grade Primary School Students' Understanding of IPAS Concepts - Pridayanti, Ni Kadek Padma; Rati, Ni Wayan; Setyowahyudi, Rendy (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Science and social learning in elementary schools is still dominated by conventional methods with limited integration of digital technology, resulting in suboptimal conceptual understanding among students. Abstract topics such as human body organs require interactive visual media to support more concrete and meaningful learning experiences. This study aims to analyze, develop, and evaluate the feasibility and effectiveness of augmented reality–based animated video media to enhance fifth-grade students’ conceptual understanding of science and social learning. The research employed a Research and Development method using the ADDIE model with a one-group pretest–posttest design. Research subjects included 2 material experts, 2 media experts, 2 teachers, and 23 students. Data were collected through validation questionnaires, response questionnaires, and concept understanding tests. Data analysis used descriptive quantitative and inferential statistics, including Shapiro-Wilk normality testing and paired sample t-test. The results showed that the developed media achieved high validity scores from material experts (3.83) and media experts (3.72), and high practicality scores from teachers (3.72) and students (3.94). Effectiveness testing indicated a significant improvement in conceptual understanding with a significance value of 0.000 (p < 0.05). Statistically, the improvement was confirmed by the paired sample t-test result of t(22) = 6.450, which was significant (p < 0.05). In conclusion, augmented reality–based animated video media is valid, practical, and effective in improving students’ conceptual understanding. The study implies that integrating augmented reality technology can serve as an innovative interactive learning strategy to improve the quality of elementary science and social learning.